Drying of sugarcane bagasse in a partially filled horizontal drum - Tada, E. F. R. [UNESP]; Bueck, A.; Casciatori, F. P.; Thomeo, J. C. [UNESP]; Carcel, J. A.; Clemente, G.; GarciaPerez, J. V.; Mulet, A.; Rossello, C. (Univ Politecnica Valencia, 2018)
One-phase model have been reported to describing the simultaneous heat and mass transfer in a horizontal drum partially filled by sugarcane bagasse with attention to the loss of water promoted by the increase of temperature. Mass and energy balances were written in MatLab language and solved by finite difference method. Predicted temporal and spatial profiles of moisture content and temperature are shown. Experimental tests were carried out in a horizontal drum and the temporal profiles were obtained. Great adjustments between experimental and predicted data were observed, indicating that the model is able to describe the transport phenomena in this system.
Keywords: horizontal drum; heat and mass balances; sugarcane bagasse; solid-state fermentation process